The cultural competence in the nursing professional: Sub-Saharan population - Isabel Gentil García (Universidad de Alicante, 2012)
Departing from the widespread idea of the need of intercultural mediators in the sanitary world as the solution to the derivative difficulties of working with persons of other cultures, this work has as aim demonstrate that the necessary thing is that the professionals of nursing we form ourselves to realize taken care culturally competent. There are analyzed certain premises without which they cannot be realized taken care competent. The fundamental thing is to have a constructive attitude towards the cultural differences and sensibility towards the persons of other cultures. Also it is necessary increase the knowledge on other cultures. By it values and beliefs are described in relation to health and disease in sub-Saharan population. Coming to the conclusion that the human beings though diverse culturally we share many common features in relation to the disease.